Research on Multiphase Flow and Nozzle Wear in a High-Pressure Abrasive Water Jet Cutting Head - Xiang Zou; Liandong Fu; Lin Wu; Wenhao Zuo (Machines, 2023)
Research on the mixing process of gas–liquid–solid multiphase flow in a high-pressure abrasive water jet (HP-AWJ) is of great significance in improving the performance of water jet cutting. In this paper, the Euler method-VOF model, a computational fluid dynamics (CFD) simulation method, is used to solve the multiphase flow of air–water in an abrasive water jet (AWJ). The Euler–Lagrange method is further used to study the multiphase flow of abrasive particles. The method considers the shape factor of the particle, uses the Rosin–Rammler function, and defines an effective model for the particle-to-wall wear model. By solving the velocity of the continuous phase and particulate phase in the AWJ cutting head, the problem of nozzle wear caused by particles is studied. Finally, the exit velocity of the AWJ and particle wear are investigated by varying the model’s parameters. The results show that the double abrasive tube model effectively improved the problem of one-sided wear inside the nozzle, and the tangential velocity of the air affected the acceleration process of the abrasive inside the nozzle, with smaller abrasive velocity resulting in less wear on the model. Simultaneously, the effects of the abrasive inlet tube and mixing chamber size on abrasive exit velocity and nozzle wear are analyzed. The results obtained provide valuable guidance for addressing the multiphase flow mixing issues in the AWJ, improving the abrasive acceleration process and extending the nozzle’s lifetime.